Risk factors for sacrococcygeal pilonidal sinus: a systematic review and meta-analysis supplemented by genetic causal assessment - Xu, Xingli; You, Peijie; Qin, Jialin; Wu, Jiong (Frontiers in Surgery, 2026)
ObjectiveSacrococcygeal pilonidal sinus (PS) is a common, chronic, and recurrent condition with unclear pathogenesis. Previous studies have primarily focused on local factors, with limited causal validation of systemic risk factors. This study aims to synthesize observational and genetic evidence to systematically evaluate potential risk factors and explore possible multisystem pathological mechanisms.MethodsThis study primarily employed a systematic review and meta-analysis by retrieving high-quality observational studies to quantitatively evaluate the associations between various risk factors—such as behavioral habits, metabolic and immune factors, and related diseases—and PS. Heterogeneity tests, subgroup analyses, and sensitivity analyses were conducted to ensure the robustness of the results. To further validate the causal nature of these associations, a two-sample Mendelian randomization (MR) analysis based on genome-wide association study (GWAS) data was performed to explore potential genetic causal relationships.ResultsA total of 19 observational studies were included, of which 12 were eligible for meta-analysis. The findings revealed that increased body mass index, sedentary behavior, dense body hair, family history, and poor hygiene were significantly associated with an elevated risk of PS. These associations were further supported by MR analyses. In addition, higher eosinophil counts and high-density lipoprotein (HDL) levels appeared to be protective factors. Conditions such as diabetes, hidradenitis suppurativa, acne, polycystic ovary syndrome, and osteoarthritis were also linked to increased PS risk. No significant associations were found between PS and smoking, alcohol consumption, sex hormones, hair color, skin color, excessive sweating, physical activity, or most lipid parameters.ConclusionThis study identified multiple risk factors for PS through meta-analysis and systematic review, and further provided genetic evidence of causality. The findings suggest that PS is not merely a localized condition but may be driven by systemic factors such as metabolic, inflammatory, and endocrine dysfunctions. These results underscore the importance of early identification of high-risk individuals and support the need for targeted lifestyle interventions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251057814, identifier CRD42024618778.